Alzheimer’s Disease in the Age of Precision Medicine: Advances in Pathophysiology, Clinical Management and Therapeutic Strategies - Piotrowski, Michał; Serwicki, Piotr; Pośpiech, Szczepan; Prosowski, Jakub; Początek, Jakub; Schendzielorz, Jessika (Quality in Sport, 2025)
Aim of the study: The aim of this study is to provide a comprehensive review of recent advancements in Alzheimer’s disease (AD), focusing on its complex pathophysiology, diagnostic methods, and emerging therapeutic strategies. Materials and methods: A detailed analysis of recent literature was conducted, reviewing major pathophysiological mechanisms including amyloid-beta accumulation, tau pathology, mitochondrial dysfunction, and chronic neuroinflammation. Diagnostic methods were evaluated, emphasizing biomarker-based approaches and the integration of artificial intelligence (AI) for improved precision in early detection. Main results: The analysis revealed that currently approved therapies, such as cholinesterase inhibitors and NMDA receptor antagonists, provide only symptomatic relief without significantly slowing disease progression. New therapeutic approaches targeting multiple pathways, including monoclonal antibodies against amyloid and tau, mitochondrial modulators, anti-inflammatory drugs, and gene therapy, show potential but face clinical validation challenges. AI-based technologies have significantly enhanced diagnostic accuracy, allowing personalized patient management and better disease staging. Conclusions: The future management of Alzheimer’s disease will likely require a multimodal strategy integrating advanced diagnostic tools, personalized therapies, and targeted interventions addressing diverse disease mechanisms. Overcoming current research limitations and healthcare accessibility issues will be critical to translating these innovations into effective clinical practice.